Cloud-to-ground lightning observations over the eastern Amazon Region - Almeida, Arthur C.; Rocha, Brígida R.P.; Souza, José Ricardo S.; Sá, José Alberto S.; Filho, José A. Pissolato (Atmospheric research, 2012)
Cloud-to-ground (CG) lightning variables, space and time distributions near the equator, over Eastern Amazon, were analyzed in this work. Over seven million lightning flash events of this type, detected by a VAISALA lightning detection network were processed. This data set was collected by the Brazilian Amazon Protection System between 2006 and 2008. The results showed the sub-areas of higher occurrence densities, polarity types, current peak intensity intervals, as well as, the hourly distributions of CG lightning, for this region. A considerable percentage (7%) of discharges with stroke current peaks above 100kA, was observed. An attempt was made to compare the statistical results of this work with observations made elsewhere in Brazil and other regions of the world. The differences found suggest that, some regional peculiarities of the CG lightning parameter values should be taken into consideration, for electric and telecommunication systems protection against atmospheric electric discharges, in the Amazon Region. ► Cloud-to-ground lightning variables distributions over Eastern Amazonia were analyzed. ► Data from 7million flashes observed during 2006 to 2008 by a LLS were processed ► Sub-areas of higher occurrence densities and hourly histograms of events were shown ► About 7% of the strokes presented peak currents above 100kA. ► This suggests the need of extra protection for the electrical systems in this region.